Penggunaan Diskresi dalam Penegakan Hukum oleh Kepolisian menurut Undang-Undang Nomor 2 Tahun 2002 tentang Kepolisian Negara Republik Indonesia - K, Roberts (Pagaruyuang Law Journal, 2019)
The important role of the National Police as a law enforcer is very necessary. However, in meetings in the field, the police are faced with a decision in which he must choose an action taken outside the limits of his authority and outside the command of his leader. At certain times, a police officer must make the right decision or better known as "discretion". A quick and precise decision is of course motivated by consideration and assistance with accountability. The implementation was relatively more important than the police officer recommended, but even so the background of the users must be of greater and wider interest (public interest).